The letters of Jesus Chris(peace be upon him)to King Abgar ( A Historical Presentation) (Journal of Imam Al-Kadhim College, 2024)
The scarce historical accounts related to the letters exchanged between Jesus Christ, peace be upon him, and King Abjara have occupied the minds of many specialists. From this standpoint, the following questions arise: Did Jesus Christ actually send letters to King Abgar , what is their content, and did the historical sources mention them, and how did history deal with them? In order to answer, the specialists say that the subject of the letters mentioned in history faced two approaches: the first sided with it and supported it, and the second rejected it based on multiple analyses. Accordingly, (this research) presents these letters in a purely historical manner, mentioning the opinions of the two groups, following the theory of (historical presentation) from Through a comprehensive, literal presentation of the letters, their content, their sources, and the doubts that were raised about them, using the (descriptive approach) by returning to the main sources that mentioned those letters, then following the rest of the resources in an accurate historical manner, with the help of a number of references that examined those letters in order to answer the questions. (The problem of research), which determines its possibilities in the era of Jesus Christ, peace be upon him, and the kingdoms neighboring Palestine in order to achieve (the goal of the research) based on a focused (historical presentation) of those letters in order to instill the spirit to re-read the unknown or hidden from Christian history according to the academic path.
Keywords: : The Letters , Edessa , Abjar , Eusabius and Addai of Edessa